Increasing physical activity, but persisting social gaps among middle-aged people: trends in Northern Sweden from 1990 to 2007 - Ann Öhman; Kerstin Söderman; Margareta Norberg; Nawi Ng (Taylor & Francis Group, 2011)
Background : Physical activity is identified as one important protective factor for chronic diseases. Physical activity surveillance is important in assessing healthy population behaviour over time. Many countries lack population trends on physical activity. Objective : To present trends in physical activity levels in Västerbotten County, Sweden and to evaluate physical activity among women and men with various educational levels. Methods : Population-based cross-sectional and panel data from the Västerbotten Intervention Programme (VIP) during 1990-2007 were used. All individuals in Västerbotten County who turned 40, 50, or 60 years old were invited to their local primary health care for a health screening. Physical activity during commuting, recreational activities, physical exercise, and socio-demographic data were collected using a self-administered questionnaire. Respondents were categorised as sedentary, moderate physically active, or physically active. Results : The prevalences of physically active behaviours increased from 16 to 24.2% among men and from 12.6 to 30.4% among women. Increases are observed in all educational groups, but gaps between educational groups widened recently. The level of sedentary behaviour was stable over the time period studied. The 10-year follow-up data show that the prevalences of physically active behaviours increased from 15.8 to 21.4% among men and 12.7 to 23.3% among women. However, 10.2% of men and 3.8% of women remained sedentary. Conclusion : Despite the promising evidence of increasing physical activity levels among the population in Västerbotten County, challenges remain for how to reduce the stable levels of sedentary behaviours in some subgroups. Persisting social gaps in physical activity levels should be addressed further. An exploration of people's views on engaging in physical activity and barriers to doing so will allow better formulation of targeted interventions within this population.